2008
DOI: 10.1242/jeb.017426
|View full text |Cite
|
Sign up to set email alerts
|

Caste-dependent sleep of worker honey bees

Abstract: SUMMARYSleep is a dynamic phenomenon that changes throughout an organismʼs lifetime, relating to possible age-or task-associated changes in health, learning ability, vigilance and fitness. Sleep has been identified experimentally in many animals, including honey bees (Apis mellifera). As worker bees age they change castes, typically performing a sequence of different task sets (as ʻcell cleanersʼ, ʻnurse beesʼ, ʻfood storersʼ and ʻforagersʼ). Belonging to a caste could differentially impact the duration, const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 40 publications
4
66
0
1
Order By: Relevance
“…Together, our findings suggest that the social signals that influence sleep include volatile pheromones, sounds, comb vibrations or other environmental variables that are associated with the activity or behavior of other bees in the colony. Our findings confirm and extend previous evidence for an agerelated decrease in honey bee sleep (Eban-Rothschild and Bloch, 2008;Klein et al, 2008;. Young bees slept more than their older sister foragers when the two groups of bees were transferred from the same colony to individual cages in the same lab environment.…”
Section: Research Articlesupporting
confidence: 89%
See 2 more Smart Citations
“…Together, our findings suggest that the social signals that influence sleep include volatile pheromones, sounds, comb vibrations or other environmental variables that are associated with the activity or behavior of other bees in the colony. Our findings confirm and extend previous evidence for an agerelated decrease in honey bee sleep (Eban-Rothschild and Bloch, 2008;Klein et al, 2008;. Young bees slept more than their older sister foragers when the two groups of bees were transferred from the same colony to individual cages in the same lab environment.…”
Section: Research Articlesupporting
confidence: 89%
“…2B, repeated measures one-way ANOVA, d.f.=3, F colony S73 =23.78; F colony H1 =17.98; F colony H14 =37.03). These findings that are based on locomotor activity data are consistent with detailed behavioral observations of sleeping honey bee foragers (Eban-Rothschild and Bloch, 2008;Kaiser, 1988;Klein et al, 2008).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Inactive foragers have long been thought to enter into sleep-like states (von Frisch, 1967;Kaiser and Steiner-Kaiser, 1983;Kaiser, 1988;Eban-Rothschild and Bloch, 2008;Klein et al, 2008); this speculation is strengthened by work in Drosophila rigorously demonstrating that insects sleep (Hendricks et al, 2000;Shaw et al, 2000) (reviewed by Harbison et al, 2009). Perhaps inactive bees are showing evidence for the kind of purging of old proteins and building of new proteins that has been associated with sleep in other organisms (reviewed by Mackiewicz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is much more known about Drosophila sleep now than in any other insect because of its genetic tractability. Studies in honeybees have shown that these insects sleep like other diurnal insects both inside of the hives (Kaiser 1988;EbanRothschild and Bloch 2008;Klein et al 2008) and under laboratory conditions (Sauer et al 2003), and that their sleep is controlled by the interaction of a circadian clock and a sleep homeostat. Like in mammals, sleep-deprived bees sleep longer the following night, a phenomenon called ''sleep rebound.''…”
mentioning
confidence: 99%